PENGAPLIKASIAN TEORI HERMENEUTIKA HANS-GEORG GADAMER TERHADAP HADIS NABI MUHAMMAD - MUH. ILHAM R. KURNIAWAN (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2021)
AbstractThe hadiths of the Prophet are present in people's lives today in a 'frozen' form and have no application. This has prompted the initiation of various breakthroughs to find a way out of the coldness for the 'native' hadith to conform to the demands of the times. One of them is through the hermeneutic approach in the interpretation of hadith. The hermeneutic approach in the interpretation of hadith can be taken through three layers of interpretation, namely: 1. Interpretation "from within" the hadith text. 2. Interpretation of the "environment" of the hadith text. 3. interpretation "against" the hadith text. From the above interpretation has a focus, objectives and methods from one another. This method is not only a tool for studying the horizon of the text (matan), but also the horizon of the initiator (Prophet), the reader (rijal al-hadith, mukharrij al-hadith, and mufassir), and their contextuality. Although hermeneutics is a "tool" (not a substitute for) various well-established hadith sciences, the hermeneutic approach is expected to produce meanings that combine elements of hadith textuality and contextuality at the same time, considering that text can only find meaning in context.Keywords: Hermeneutic, Native, Frozen  AbstrakHadits Nabi hadir dalam kehidupan masyarakat saat ini dalam bentuk 'beku' dan tidak memiliki aplikasi. Hal ini telah mendorong pencetusan berbagai terobosan untuk mencari jalan keluar dari kebekuan tersebut demi 'pribumi' hadits agar sesuai dengan tuntutan zaman. Salah satunya melalui pendekatan hermeneutik dalam tafsir hadits. Pendekatan hermeneutik dalam tafsir hadits dapat ditempuh melalui tiga lapis tafsir, yaitu: 1. Penafsiran “dari dalam” teks hadits. 2. penafsiran “lingkungan sekitar” teks hadits. 3. penafsiran “ yang melawan” teks hadis. Dari tafsir di atas mempunyai fokus, sasaran dan metode antara satu dengan yang lainnya. Metode ini tidak hanya sebagai alat untuk mempelajari cakrawala teks (matan), tetapi juga cakrawala pemrakarsa (Nabi), pembaca (rijal al-hadits, mukharrij al-hadits, dan mufassir), serta kontekstualitasnya. Meskipun hermeneutika merupakan “alat” (bukan pengganti) berbagai ilmu hadits yang sudah mapan, namun pendekatan hermeneutika diharapkan menghasilkan makna yang menggabungkan unsur tekstualitas dan kontekstualitas hadits pada saat yang bersamaan, mengingat teks hanya dapat menemukan makna dalam konteks.Kata Kunci: Hermeneutik, Pribumi, Beku